A DIGITAL COMIC APPROACH TO IMPROVING STUDENTS' ABILITY TO READ AND UNDERSTAND STORIES - Fariz, Andi Naufal Ahmad; Atmowardoyo, Haryanto; Muhalim, Muhalim (JTechLP: Journal of Technology in Language Pedagogy, 2026)
This research aimed to ascertain if digital comics enhance students' reading comprehension of narrative texts. This study employed a quantitative methodology utilizing a quasi-experimental design. The data for this research were collected using pre-tests, post-tests, and in-depth interviews. The data analysis procedures employed were the Wilcoxon signed-rank test and the Mann-Whitney U test. The Wilcoxon Signed-Rank analysis yielded an Asymp.Sig (2-tailed) of 0.663, exceeding α = 0.05, while the Mann-Whitney U analysis produced an Asymp.Sig (2-tailed) of 0.668, also surpassing α = 0.05. It can be established that digital comics do not enhance students' reading comprehension of narrative texts. In-depth interviews were performed to ascertain the causes of the notable decrease in the scores of numerous students. The findings from the in-depth interviews revealed that insufficient vocabulary comprehension, linguistic challenges, disparities in fundamental abilities between the experimental and control groups, difficulties in concentration, and the researcher's explanation of the material were contributing factors.